Casting distortion of five-fixture supported implant frameworks fabricated on master casts - Mitha, Tasneem (My University, 2008)
Statement of the problem: Conventional techniques for implant framework fabrication have been shown to produce errors that are inconsistent with the passive-fit requirement for osseointegrated implant frameworks. Purpose: The aim of this study was to assess the three-dimensional distortion inherent in casting of full arch, screw-retained titanium implant frameworks. Materials and methods: A conventional commercial laboratory one-piece casting, using the lost-wax technique was used. Five wax patterns were fabricated on a die-stone cast poured from a plaster impression of a five-fixture brass analogue. A reflex microscope was used to determine the three-dimensional casting error, by measuring horizontal and vertical distances for each wax pattern and its corresponding cast titanium framework, as well as offset distances from the horizontal reference plane. Results: Significant differences were found in the amount of distortion between wax patterns and cast frameworks, with the castings being approximately 416 μm to 477 μm larger than the wax frameworks. The greatest amount of distortion occurred at the terminal implant abutments, and in the vertical dimension. However, there was inconsistency in these differences, indicating the three-dimensional nature of the overall distortion of the cast frameworks. Conclusions: It is doubtful whether any conventionally cast framework can be made to the degree of accuracy required to fit passively on its abutments because of the multiple variables inherent in this process. It is therefore recommended that all full-arch, cast titanium frameworks be cast in sections, or alternatively be sectioned, indexed and soldered before being seated intraorally.
Keywords: casting distortion; implant frameworks